An assessment of survey methodology, calling activity, and habitat associations of wood frogs (rana sylvatica) and boreal chorus frogs (pseudacris maculata) in a tundra biome - Mannan, Robert N. (2008)
The tundra biome near Cape Churchill, Manitoba is being influenced by global climate change and herbivory from an increasing population of light geese. These environmental changes may impact anuran populations, although little is known about population trends in anurans in the region. The isolation of the region may render traditional anuran survey methods ineffective. I tested two methods of surveying for two anuran species, boreal chorus frogs (Pseudacris maculata) and wood frogs (Rana sylvatica). I solicited calls from non-calling anurans by manually broadcasting conspecific advertisement calls, and I used automated audio recorders to increase survey coverage. I detected 0.38 additional wood frogs per survey when broadcast calls were employed, compared to surveys without broadcasts. I was unable to detect additional boreal chorus frogs by broadcasting conspecific advertisement calls. Using automated audio recorders, I was able to identify anuran presence in a radius of 100 m, but detections of wood frogs were low compared to manual surveys. I suggest that broadcasts of wood frog advertisement calls be implemented into surveys for wood frogs in the tundra biome, and that additional research is necessary to determine whether solicitation can be used to increase detection of other anuran species. Chapter II Little information exists regarding wood frogs (Rana sylvatica) and boreal chorus frogs (Pseudacris maculata) in the tundra biome, where environmental conditions differ from most of the rest of their breeding ranges. Understanding anuran calling patterns is essential to most anuran survey methodology. During the summer of 2007, I placed automated audio recorders at anuran breeding locations and recorded number of calling anurans near Cape Churchill, Manitoba. I used data loggers and automated call recorders to document date, time of day, temperature, and relative humidity. Automated recorders detected wood frogs between 30 May and 2 July 2007, and boreal chorus frogs between 11 June and 5 July 2007. Calling ...